Cysts and parasites in an abattoir in Northwest Ethiopia; an urgent call for action on “one health” - Getahun, Desalegn; van Henten, Saskia; Abera, Adugna; Senkoro, Mbazi; Owiti, Philip; Lombamo, Fantu; Girma, Blen; Ashenefe, Baye; Deressa, Asefa; Diro, Ermias (The Journal of Infection in Developing Countries, 2020)
Introduction: Zoonotic parasitic infections such as echinococcosis affect cattle, sheep and goats by lowering quality of meat and hides as well as decreasing milk production. The burden of such diseases among humans is usually underestimated as they are difficult to diagnose. We used abattoir data to estimate the prevalence of zoonotic parasitic infections in animals. Methodology: Data from 2005-2018 was used from the registry of an abattoir in Northwest Ethiopia. Frequencies, proportions and trends over time were analyzed. Meat inspection was conducted by visualization, palpation and incision. Results: A total of 58,787 animals were slaughtered in the abattoir during the study period. These included 51,956 (88 %) cattle, 5,890 (10%) sheep and 941 (2%) goats. The detected parasites included Echinococcus in 12,334/58,787 (21%) and Fasciola in 10,551/58,787 (18%) animals. Echinococcus infection was highest among goats (267/941, 28%), followed by cattle (11,591/51,956, 22%) and sheep (476/5,890, 8%). Fasciolosis was detected in 9,877/51,956 (19%) cattle and 178/941 (19%) goats. The number of animals slaughtered strongly decreased over time from 8,405 in 2006 to 1,605 in 2018. However, the proportion of parasitic infections remained high with some fluctuations over the study period. Conclusions: Echinococcosis and fasciolosis were very common with one out of five animals slaughtered infected. This is of public health concern and needs urgent multi-sectorial efforts from stakeholders at the national and regional level for control of these diseases. One health program approaches may warrant the control of transmission to humans.